IMPLEMENTASI TERAPI RELAKSASI BENSON UNTUK PENINGKATAN SATURASI OKSIGEN PADA PASIEN TUBERKULOSIS PARU DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Wulandari, Anggy; Susyanti, Deni; Vitu, Handerman (SINERGI : Jurnal Riset Ilmiah, 2025)
Pulmonary tuberculosis is a contagious infectious disease that attacks the respiratory system and often causes a decrease in oxygen saturation in the body. Reduced oxygen saturation can worsen the patient's condition and hinder the healing process. Therefore, an intervention is needed to help increase oxygen levels in the blood. One non-pharmacological method that can be used is Benson relaxation therapy, which aims to reduce stress and improve respiratory function through deep breathing techniques and positive suggestions. This study aims to determine the effectiveness of Benson relaxation therapy in increasing oxygen saturation in patients with pulmonary tuberculosis. The study used a descriptive method with a case study approach involving two patients. The observations showed that after undergoing Benson relaxation therapy for three consecutive days, both patients experienced an increase in oxygen saturation. In the first patient, oxygen saturation increased from 91% on the first day to 95% on the third day. In the second patient, it increased from 92% to 96% during the same period. These results indicate that Benson relaxation therapy can be an effective independent nursing intervention to help improve oxygen saturation in patients with respiratory disorders such as pulmonary tuberculosis. This therapy can also be easily applied in various healthcare settings